Local distribution pattern of Virga pilosa (L.) Hill. (Dipsacaceae) as an effect of its life and dispersal strategy - Bernard, Rafał; Chmiel, Julian (Biodiversity: Research and Conservation, 2020)
A new locality of regionally alien and rare Virga pilosa was recorded outside the compact range of the species in the Wielkopolski National Park, midwestern Poland. It probably appeared as a result of unintentional anthropochory. Local distribution pattern of V. pilosa in micro- and mesoscale was described and interpreted in the light of life and dispersal strategy and habitat conditions of the species. Accidental epizoochory and unintentional anthropochory could have been responsible for the mesoscale distribution pattern with population units scattered along human and animal communication routes. Close dense autochory together with the species CR life strategy with a strong competitive component were responsible for microscale distribution pattern alternating in space and time, but always mosaic, including vegetative, generative and mixed patches. The distribution pattern was also influenced by the occurrence of the required combination of the moderately light, moderately moist and nitrogen-rich habitat conditions with favourable human-induced disturbance. Some data on the form of growth, reproductive potential and dispersal mode of the species, as well as on plant-animal interactions were also included.